Supporting adjective learning by children with Developmental Language Disorder: Enhancing metalinguistic approaches. Issue 2 (30th November 2022) - Davies, Catherine; Ebbels, Susan; Nicoll, Hilary; Syrett, Kristen; White, Sarah; Zuniga‐Montanez, Cecilia
Abstract: Background: Adjectives are essential for communication, conceptual development and academic success. However, they are semantically and syntactically complex and can be particularly challenging for children with Developmental Language Disorder (DLD). Surprisingly, language interventions have not typically focused on this important word class. Aims: (1) To provide a supportive and accessible primer on adjectives for practitioners; (2) to explore how the SHAPE CODING TM system can be adapted to support adjective learning in DLD; and (3) to provide practical recommendations on how to support adjective learning in clinical practice and education. Methods/Procedure: We synthesise linguistic and psychological research on adjective semantics, clinical insights into DLD and pedagogical practice supporting this population. Main Contribution: We address the lack of specific training in the nature and acquisition of adjectives for speech and language therapists (SLTs) by providing an accessible primer. We also provide an innovative guide detailing how an established metalinguistic intervention might be adapted to support adjective learning. Conclusions/Implications: Without targeted support for adjective learning, the communicative potential of children with DLD is compromised. Our recommendations can be used across a range of therapeutic and educational contexts to guide SLTs and teaching staff in developing practice in this area. What this paper adds: What is already known on the subject: Adjectives are an essential word class needed for effective communication. They are also vital to successfully achieve academic objectives across all curriculum areas. For example, most subjects require children to be able to describe, evaluate, compare and discriminate different events, objects or techniques. Children with Developmental Language Disorder (DLD) have deficits in various domains of language that can affect adjective learning and use. What this paper adds to existing knowledge: Despite the importance of adjectives, speech and language therapists (SLTs) and other professionals supporting language development rarely receive specific training regarding their structure and meanings, and how to teach and support their use. This article provides an accessible primer on the many subtypes of adjectives and how these behave syntactically and semantically. It explores how adjective teaching could be enhanced for children with DLD by adapting an established metalinguistic technique and provides practical recommendations for implementing this approach. What are the potential or actual clinical implications of this work?: By raising awareness of the complexities of adjectives and providing strategies to support their acquisition by children with DLD, this article will enable SLTs and teaching staff to improve their understanding and practice in this area and, with further research, to develop robust, effective interventions for children with DLD. This will contribute to enhancing the long‐term academic, social and employment success of children with DLD.